Analysis of the Accounting Information System of Toman Bakery MSMEs Simpang Tanjung Medan Sunggal - Noviani; Irawan; Sri Wahyuni; Miftahurrahmah Sinaga (Yayasan Multidimensi Kreatif, 2024)
An accounting information system is a collection of resources, such as people and equipment, that have been designed to convert financial data and other data into information. The existence of an Accounting Information System for MSMEs will be one of the means to compile various reports that are indispensable for MSMEs. This research was conducted on MSMEs Tomang Bakery, Simpang Tanjung Village, Medan Sunggal District, the purpose of this study is to analyze and evaluate the accounting information system applied to MSMEs Tomang Bakery, Simpang Tanjung Village, Medan Sunggal District. The type of research used in this study is qualitative, while the methods used in data collection are by conducting interviews, observations and documentation. From the results of this study, the accounting information system implemented by MSMEs Tomang Bakery Simpang Tanjung Village, Medan Sunggal District is still classified as manual and not in accordance with EMKM financial accounting standards so that it still has many shortcomings and makes it difficult for owners to make decisions and the financial statements are difficult to read both from internal and external parties